Tectonic deformation in the Tyrrhenian: A novel statistical approach to infer the role of the Calabrian Arc complex. Issue 11 (27th November 2015) - Splendore, Raffaele; Marotta, Anna Maria; Barzaghi, Riccardo
Abstract: A thermomechanical model is used to analyze the strain pattern due to the Africa‐Eurasia convergence in the area that extends from the Calabrian Arc to the Alpine domain and the role that is played by the Calabrian Arc complex in controlling the northward propagation of the tectonic stress. After a preliminary analysis to eliminate GPS stations that are not representative of the main regional tectonic process, the predicted deformation is compared to that based on GPS observations by using a novel χ 2 test in which both data and model uncertainties are taken into account. A large amount of the tectonic force (at least 75%) that is associated with the Africa‐Eurasia convergence is accommodated by the Calabrian Arc complex, which plays a crucial role in controlling the intraplate propagation of the stress in the south Tyrrhenian area. Furthermore, a strong lithosphere, which is characterized by a granite‐type upper crust, diabase‐type lower crust, and peridotite‐type lithosphere mantle, must pave the south Tyrrhenian; and a soft lithosphere, which is characterized by a granite‐type upper crust, granulite‐type lower crust, and peridotite‐type lithospheric mantle, must pave the surrounding area to reproduce the expected regional compression in the SE‐NW direction and extension in the perpendicular direction. Finally, the local deformation at high latitudes is not sensitive to variations in the boundary conditions along a limited portion of the Calabrian Arc. Key Points: We infer the role of the Calabrian Arc in the northward propagation of tectonic stress An outlier detection scheme enabled the identification of nonrepresentative GPS stations An important portion of the Africa‐Eurasia convergence is not transmitted through the Calabrian Arc